Evaluating the Effect of Control Flow on the Unit Testing Effort of Classes: An Empirical Analysis. (14th June 2012) - Badri, Mourad; Toure, Fadel
Abstract : The aim of this paper is to evaluate empirically the relationship between a new metric ( Quality Assurance Indicator —Qi) and testability of classes in object-oriented systems. The Qi metric captures the distribution of the control flow in a system. We addressed testability from the perspective of unit testing effort. We collected data from five open source Java software systems for which JUnit test cases exist. To capture the testing effort of classes, we used different metrics to quantify the corresponding JUnit test cases. Classes were classified, according to the required testing effort, in two categories: high and low. In order to evaluate the capability of the Qi metric to predict testability of classes, we used the univariate logistic regression method. The performance of the predicted model was evaluated using Receiver Operating Characteristic (ROC) analysis. The results indicate that the univariate model based on the Qi metric is able to accurately predict the unit testing effort of classes.